Epidemiology, Clinical Pattern and Management Outcome of Paediatric Burn Injuries in Nepal - Thapa, Bijay; Chapagain, Ram Hari; Kayastha, Anju (Journal of Nepal Paediatric Society, 2021)
Introduction: Burn injuries are third commonest type of injury in Nepal and 61% of burn victims are children. This represents a significant morbidity and mortality burden for patients and families. This study was carried out to describe epidemiology, clinical pattern and therapeutic outcome of children with burn. Methods: It is a retrospective observational study of routinely collected data of children up to 14 years admitted to the Burns Ward at Kanti Children’s Hospital, Kathmandu, Nepal, from July 2016 to July 2019. Statistical analysis was done on the collected data. Results: Total 935 patients were admitted with an average of 311.7 per year, among which 63% were males and 83.0% were aged five years or under. Patients travelled from all over Nepal for treatment at this hospital. 50.6% of patients presented with fresh burns < 24 hours after injury. Scald burn was the commonest (82.6%). Children under five were more likely to have scald burns, whereas older children more likely to have flame or electric burns. Majority of cases (70%) were of mild burns < 10% TBSA and only 3.2% TBSA > 30%. 68.5% were managed conservatively and 18.4% required debridement and skin grafting. Mean length of stay was 15 days. Overall mortality was 1.0%. In children with > 30% burns mortality was 12.9%. Conclusions: Scald burn was the commonest while proportion of flame burn increases with age. Majority of burns occur in male under five years of age. Most cases presented with < 10% TBSA and were managed conservatively.